Parents’ attitudes towards inclusion of sexuality education in Malaysian schools - Makol-Abdul, Pute Rahimah; Nurullah, Abu Sadat; Imam, Syed Sohail; Abd Rahman, Saodah (European Network about Parents in Education, 2009)
The present study examined the attitudes of Malaysian rural parents regarding sexual health education in elementary schools. Using a comprehensive list of sex education topics, parents were asked to examine which topics they believed should be taught at schools. In addition, the study also assessed the relationship between parents’ demographic characteristics such as age, gender, education, and occupation and their approval of sexual health education. The respondents of the study included parents (n=211) of children registered in four selected schools in Kedah, Malaysia. The majority of them (73%) supported the inclusion of various sexual health topics in school curriculum provided the contents were in line with religious teachings. The study has generated important empirical findings regarding local community’s response to school-based sexuality education. This information is needed in facilitating the development of sexual health policy at various institutional levels, and in the effective implementation of sexual health curriculum in Malaysian schools.